1992
DOI: 10.1093/treephys/10.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Storage and internal cycling of nitrogen in relation to seasonal growth of Sitka spruce

Abstract: Three-year-old clonal cuttings of Picea sitchensis (Bong.) Carr. were grown for two years (1988-1989) in sand irrigated with a nutrient solution containing either 1.0 mol N m(-3) (low N) or 6.0 mol N m(-3) (high N) NH(4)NO(3). In 1988, all the N provided was enriched with (15)N to 4.95 atom % (labeled N). In 1989, N was supplied with (15)N at natural abundance (unlabeled N). The recovery of unlabeled and labeled N in new foliage was used to quantify the internal cycling of N. In the high-N treatment, trees had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 22 publications
8
74
1
1
Order By: Relevance
“…Carr. ), it was demonstrated that trees grown at low N conditions remobilised a bigger proportion of N from roots than trees grown at high N conditions [18], affecting nitrogen partitioning.…”
Section: Carbon/nitrogen Equilibriummentioning
confidence: 98%
“…Carr. ), it was demonstrated that trees grown at low N conditions remobilised a bigger proportion of N from roots than trees grown at high N conditions [18], affecting nitrogen partitioning.…”
Section: Carbon/nitrogen Equilibriummentioning
confidence: 98%
“…In contrast to deciduous trees, carbohydrate stores remain relatively constant in evergreen species throughout winter Höll 1991, 1992), whereas lipids may accumulate (Sudachkova et al 2004). A remobilization of N from older shoots (Salifu and Timmer 2003) or the needles from the previous year (Millard and Proe 1992) provides the N necessary for the growth of newly formed tissues. Fluctuations of N reserves in evergreen species have not been well studied for the rest of the year but appear to be less variable than those of C reserves (Millard and Grelet 2010).…”
Section: The Phenology Of Carbon and Nitrogen Reservesmentioning
confidence: 99%
“…A seasonal course of N contents similar to that in beech roots has previously been observed in above-ground parts of beech and spruce trees, with maximum N transport in xylem (Glavac & Jochheim, 1993 ;Dambrine et al, 1995 ;Schneider et al, 1996) and phloem immediately before and during bud break. The N supply of newly developing tissues of trees during spring can at least partly be met by remobilization of internal N sources from storage tissues (Millard & Proe, 1992 ;Millard, 1994). During this period of time N uptake by roots seems to be of minor significance (Millard, 1996 ;Geßler et al, 1997).…”
Section: Differences In Tsnn Contents In Beech and Spruce In Spring Mmentioning
confidence: 99%